Komunikacja interpersonalna w interakcjach społecznych - Frydrychowicz, Stefan (Człowiek i Społeczeństwo, 2020)
This article concentrates on the characterization of the transition from social interactions to interpersonal communication. For this purpose analysis of the structure of communication process was conducted on two levels: general and specific. The former focuses on the conditions of the transition from interaction to communication, and further to contact. The latter offers the analysis of the dimensions of interpersonal communication. The conclusion deals with the importance of interlocutors’ intentionality as well as appropriate regulation and coordination of the dimensions of communication for effective communication.